The use of implementation mapping in healthcare settings: a scoping review - Warhurst, Kym; Tyack, Zephanie; Beckmann, Michael; Abell, Bridget (Frontiers in Public Health, 2025)
BackgroundImplementation Mapping is a structured, theory-informed approach designed to facilitate the selection and tailoring of implementation strategies to improve the uptake of healthcare interventions. Despite growing use in healthcare settings since being introduced in 2019, there has been limited synthesis of the application or effectiveness of Implementation Mapping. This scoping review aimed to explore the extent and type of evidence that uses Implementation Mapping methodology to implement programmes or practices in healthcare settings to identify common approaches, benefits, challenges, and future directions.MethodsA systematic search was undertaken in March 2023 and updated in August 2024 across four electronic databases (MEDLINE, Embase, Scopus and CINAHL) using “Implementation Mapping” as a key word. This was supplemented with citation tracking (including the paper originally describing Implementation Mapping), manual searches of key journals, and a Google scholar search. Studies were included if they reported the use of Implementation Mapping to design and implement healthcare programmes or practices.ResultsThe review identified 32 relevant publications, reporting on 29 unique studies, primarily conducted in the United States. Implementation Mapping has been applied across a diverse range of healthcare settings, with common applications in chronic disease management, cancer care, mental health, and allied health interventions. There was notable variation in the application and reporting of Implementation Mapping. The prioritisation of determinants and implementation strategies was inconsistently described, and evaluation of implementation outcomes was often lacking. Despite these challenges, Implementation Mapping was found to provide a structured and participatory approach to implementation planning, promoting stakeholder engagement and the integration of theories, models and frameworks.DiscussionImplementation Mapping appears to be a valuable tool for guiding the selection and adaptation of implementation strategies in healthcare, but its application remains inconsistent. Greater standardisation in reporting, enhanced methodological guidance, and broader geographic and contextual diversity in studies are needed to maximise its impact. Future research should focus on evaluating the clinical and implementation outcomes associated with Implementation Mapping to establish the effectiveness of this approach in improving healthcare practices. Approaches for prioritising determinants and strategies in Implementation Mapping are suggested based on the findings and other literature.